DESAIN PRODUK MEJA BELAJAR LESEHAN ERGONOMIS DENGAN MENGGUNAKAN DATA ANTROPOMETRI DI MDTA MIFTAHUL HUDA TASIKMALAYA - Salim; Ajeng Sabarini Muslimah; Enong Siti Komariah (Cipasung Techno Pesantren: Jurnal Ilmiah, 2022)
The desk is one of the media as an intermediary facility to help the student learning process at school and is one of the indispensable needs in every school in Indonesia. Based on observations at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Miftahul Huda Tasikmalaya, that there are about 65% of children complain that they feel pain in the back and neck due to sitting hunched over during learning, by not using a study table. Therefore, the research was conducted on how to design an ergonomic lap study desk based on the anthropometric dimensions of the child's body at Madrasah Diniyah Takmiliyah Awaliyah (MDTA) Miftahul Huda. The results of the research and data processing of the dimensions of the child's body made the design of a lap study desk with the Ergonomic Design Process method which will help related institutions to design an ergonomic lap study desk for MDTA Miftahul Huda children and similar schools in Tasikmalaya so that learning activities are comfortable for children.